Azobenzene‐Based Photoswitches Facilitating Reversible Regulation of Kinesin and Myosin Motor Systems for Nanotechnological Applications. Issue 6 (17th April 2019) - Amrutha, Ammathnadu S.; Sunil Kumar, K. R.; Tamaoki, Nobuyuki
Abstract: The past decade has witnessed several significant efforts made towards implementing the biomolecular functions of motor proteins for nanotechnological applications. However, employing motor protein systems in artificial environments demands for a precise and flexible spatiotemporal control mechanism. Light being an ideal external stimulus offers major advantages, allowing better spatial and temporal resolution compared to other diffusion‐based approaches. Robust photochromic properties of azobenzene make it a prime candidate that could be incorporated into biologically active molecules to realize two‐way regulation of motor protein function. In this Minireview, we summarize the design strategies of azobenzene‐based photoswitches for reversibly regulating kinesin‐ and myosin‐driven shuttle movements and briefly discuss photoisomerization‐induced modulation in motor protein activity. Abstract : Lights, camera, action ! Different design strategies for azobenzene‐based photoswitches for application in the reversible regulation of motor protein (kinesin and myosin) driven shuttle movement are described and photoisomerization‐induced change in motor protein activity is discussed.